Soil tillage methods by years interaction for dry matter of plant yield of maize (Zea mays L.) using additive main effects and multiplicative interaction model - Jan Bocianowski; Piotr Szulc; Kamila Nowosad (Journal of Integrative Agriculture)
The objective of this study was to assess soil tillage methods by years interaction for dry matter of plant yield of maize (Zea mays L.) grown in West Poland by the additive main effects and multiplicative interaction model. The study comprised four soil tillage methods, analysed in 12 years through field trials arranged in a randomized complete block design, with four replicates. Dry matter of plant yield of the tested soil tillage methods varied from 86.7 dt ha−1 (for no-plough tillage in 2005) to 246.4 dt ha−1 (for complete conventional tillage in 2012), with an average of 146.6 dt ha−1. In the variance analysis, 49.07% of the total dry matter of plant yield variation was explained by years, 12.69% by differences between soil tillage methods, and 10.53% by soil tillage methods by years interaction. Dry matter of plant yield is highly influenced by soil tillage methods by years factors.